A História nas pegadas do "Seu" Kilowatt: as relações entre Brasil e EUA por meio da AMFORP (1936-1965) - Grandson, Douglas Edward Furness (2022)
This thesis is dedicated to political-economic-culture relations between Brazil and EUA through the multinational of eletrical services, transports and telephony, The American & Foreign Power (AMFORP). Using the image proposed by Peter Burke (2004), the research effort was to articulate the publicity studying of the multinational with the brazilians’ reactions to the venture’s performance in Brazil enterprise. Therefore, the discourse analysis adapted for historians of Ciro Cardoso (1997) and the concepts proposed by Andre R.V.V. Pereira (2015) of notions, values and concepts worldviews (Mental structure); Project (conjuncture), and advertisements (narratives) are expensive to the historiographical effort of this research. Thus, the research trajectory starts from the AMFORP instrument in Brazil, the “Seu” Kilowatt, an advertising character who worked in the concession areas of AMFORP subsidiaries and who had educational and political functions. After identifying the character's performance in Espírito Santo, the experiences brought by the company to Brazil in five more states are analyzed, an effort that had the contribution of the content analysis proposed by Laurence Bardin (1977) for the categorization of images. After identifying that the company has relegated the effort to sell products and services to the background, giving priority to the defense of public criticism for 18 years of its trajectory in Brazil, an analysis of the speeches of Brazilians about the company is undertaken, with emphasis on to the period after World War II. After the end of the conflict, the country went through a process of redemocratization that made it possible for the regional political-economic elites to confront the power of the foreign company, which was in turn prepared to contain criticisms made to its interests, which was mobilized by a multidivisional business structure (SAES, 2021). After identifying that the company relegated its efforts to the background, from 1945 to 1965, the discursive “nodes” generated around the company in the main regional newspapers are analyzed, in order to capture the regularities of the company’s narrative and its conjunctural nuances of which the following moments were remarkable: from 1945 to 1949 there were clashes; from 1950 to 1955 the first combats, and from 1955 to 1962 the major combats. After combining the analysis of the advertising image with the action of the company's managers and confronting the narratives of Brazilians with the international private initiative, the interests of the company in Brazil were addressed, in possession of the reports of AMFORP in the USA and of Companhia Auxiliar das Empresas Elétricas Brasileiras. (CAEEB), headquartered in Rio de Janeiro. I supported me on the approach of Alberto Moniz Bandeira (2011), on the emerging rivalry between Brazil and the USA and on the literature compiled by Bielschowsky (2004) on Brazilian economic thought, it was possible to reach the thesis that there was a dissimulation of the business agents of AMFORP on the impossibility of balancing international private interests with national public ones, which generated serious conflicts between Americans and Brazilians. The capacities of regional reaction to business power in the field of the public sphere were measured, in which the states of Rio Grande do Sul and Pernambuco showed a greater capacity to close unanimity around the Brazilian role in the sector and to confront the company, while Rio Grande do Norte, Espírito Santo, Rio de Janeiro and Paraná faced the inconvenience of difficulties related to electricity, transport and telephony services, generated by the lack of private investment and the delay in solving the problems of services by the multinational.